Improved Differentiation Towards Insulin Producing Beta-Cells Derived from Healthy Canine Pancreatic Ductal Organoids - Boyd H. T. Gouw; Flavia C. M. Oliveira; Hans S. Kooistra; Bart Spee; Lisa van Uden; Louis C. Penning (Veterinary Sciences)
Background: Diabetes mellitus (DM) is a common potentially life-threatening endocrine disorder in pets and humans. Since only symptomatic treatment is available, a more sustainable treatment is urgently needed. Objective: The aim of this study is to establish functional differentiated canine pancreatic β-cells that release insulin upon glucose stimulus. Methods: Pancreatic tissue was obtained from surplus material of healthy dogs (n = 4), euthanized for non-pancreatic related research. Ductal cells were isolated and expanded in dog pancreas expansion media (dpEM) and differentiated and maturated in five sequentially added pancreas differentiation media (PDMs). Gene expression was analyzed by reversed transcriptase qPCR (RT-qPCR), and insulin release was analyzed with a canine-specific ELISA. Results: Canine pancreatic ductal cells (LGR5 and SOX9 expression) were differentiated into β-cells expressing key β-cell-related genes: Pancreatic and duodenal homeobox 1 (PDX1), NK6 Homeobox 1 (NKX6.1), Glucose Transporter Type 2 (GLUT2), Proprotein convertase subtilisin/kexin type 1 (PCSK1), and low levels of insulin. Neither Glucagon (α-cells) nor LGR5 and SOX9 were expressed, and somatostatin was expressed at low levels. The differentiated cells released insulin upon glucose stimulation. Conclusion and implications: The step-by-step differentiation protocol, mimicking pancreatic organogenesis, resulted in β-cells secreting insulin levels suitable for β-cell disease modelling. It remains to be seen if stem cells from diseased animals behave similarly.